Silvertown : the Lost Story of a Strike that Shook London and Helped Launch the Modern Labor Movement. - Tully, John (Monthly Review Press, 2014)
In 1889, Samuel Winkworth Silver's rubber and electrical factory was the site of a massive worker revolt that upended the London industrial district which bore his name: Silvertown. Once referred to as the "Abyss" by Jack London, Silvertown was notorious for oppressive working conditions and the relentless grind of production suffered by its largely unorganized, unskilled workers. These workers, fed-up with their lot and long ignored by traditional craft unions, aligned themselves with the socialist-led "New Unionism" movement. Their ensuing strike paralyzed Silvertown for three months. The st